Akurasi Kompetensi Sosial Dosen dalam Pembelajaran (Studi Pada Dosen UNSA Sumbawa Besar) - Sulindra, I Gusti Made (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The purpose of this research is to know the accuracy of lecturer’s social competence in learning which includes the ability to express the opinion, the ability to accept criticism of suggestion and opinion of others, to know the students better as learners, easy to get along among the peers, employees and students, tolerance to diversity college student. The research was done by exspost facto with sampling technique using purposive sampling. Collecting and recording the scores of all aspects of lecturer’s social competence from various assessors. Then analyzed statistically described the Mean and Standard Deviasinya, estimated with the level of significance (ts) 5% using the formula Mp = Mo ts. , correlated with Product Moment correlation formula is rXY =, calculated its determination with 100% formula. Based on data analysis, it can be concluded that (1) Social Competence of lecturer in learning is Very Good; (2) The accuracy of lecturer’s social competence in learning is high, with value 0,678 - 0,848, which is estimated at all lecturer UNSA 0,606 - 0,897, with determination value equal to 45,97 - 71,91%. From the conclusion of this analysis also found that still around 2.7 - 9.7 or 3 - 10 assessors declared the social competence of lecturers in learning-not good even very bad ". Similarly found inaccuracy of social competence of lecturers in learning 28.09 - 54.03% spread across all aspects of social competence of lecturers in learning. On the basis of the results of this study is considered necessary efforts to develop the social competence of lecturers through institutional and institutional scientific activities, as well as through the independent creativity of individual lecturers